Spherical array acoustic impulse response simulation - Jarrett, Daniel P.; Habets, Emanuël; Naylor, Patrick A. (Theory and Applications of Spherical Microphone Array Processing, 2017)
In order to evaluate spherical array processing algorithms comprehensively under many different acoustic conditions, it is indispensable to use simulated acoustic impulse responses (AIRs) to characterize the source–microphone acoustic channel, most typically in a room or other enclosed acoustic environment. The image method proposed by Allen and Berkley is a well-established way of doing this for point-to-point AIRs with sensors in free space. However, it does not account for the acoustic scattering introduced by a rigid sphere. In this chapter, we present a method for simulating the AIRs between a sound source and microphones positioned on a rigid spherical array. In addition, three examples are presented based on this method: an analysis of a diffuse reverberant sound field, a study of binaural cues in the presence of reverberation, and an illustration of the algorithm’s use as a mouth simulator.
CRIS-Team Scopus Importer:2021-04-30
Keywords: Interaural Time Difference; Reverberation Time; Rigid Sphere; Sound Source; Spherical Harmonic Expansion